PENERAPAN PENILAIAN KINERJA PADA TREND INDUSTRI 4.0 - David Irawan (Parsimonia - Jurnal Ekonomi dan Bisnis, 2021)
Human resources are the most valuable asset in the running of industry. In its implementation, performance needs to be managed so that what is done is carried out efficiently. Performance management is important in the industrial world. One form of performance management is performance appraisal. Performance appraisal allows companies to measure the achievements of employees during a certain period. This can be a reference for the company to take policies in the future. In its implementation, performance appraisal requires a set of tools such as forms or questionnaires. Along with the times, the internet offers convenience that we can use to carry out activities both in daily activities to activities in the industry. Therefore, this article discusses how companies apply performance appraisal along with the times.